DAKWAH ISLAM DENGAN PENDEKATAN BIMBINGAN DAN KONSELING - Siti Prihatiningtyas (Jurnal Ilmu Dakwah, 2018)
Humans need the help of others in solving their life problems. Life problems always develop, along with the times. The problems faced by humans also change. This change provides a treatment from various parties, including da'wah as an alternative way to solve human problems. Da'wah with various elements has responsibility in solving human problems. Da'wah is carried out by various means, one of which is guidance and counseling, both of which are used as references in carrying out da'wah. Something that is needed now is to increase the role of da'wah with guidance and counseling, so as to be able to solve human problems. This article focuses on the elaboration of guidance and counseling in solving human problems within the framework of da'wah **** Manusia memerlukan bantuan orang lain dalam menyelesaikan persoalan hidupnya. Persoalan kehidupan selalu berkembang, seiring dengan perkembangan zaman. Persoalan yang dihadapi manusia juga mengalami perubahan. Perubahan ini memberikan sebuah perlakuan dari berbagai pihak, termasuk dakwah sebagai alternatif jalan menyelesaikan masalah manusia. Dakwah dengan berbagai unsurnya mempunyai tanggungjawab dalam menyelesaikan persoalan manusia. Dakwah dilakukan dengan berbagai jalan, salah satunya adalah bimbingan dan konseling, Kedua hal ini dijadikan sebagai referensi dalam melaksanakan dakwah. Sesuatu yang dibutuhkan saat ini adalah meningkatkan peran dakwah dengan bimbingan dan konseling, sehingga mampu menyelesaikan masalah manusia. Artikel ini fokus pada elaborasi bimbingan dan konseling dalam menyelesaikan persoalan manusia dalam kerangka dakwah.